PERSEPSI MAHASISWA TERHADAP PENGGUNAAN APLIKASI SYAM-OK - Siti Nur Fadillaturrisqui; Usman Usman (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2022)
Student Perceptions of the Use of the SYAM-OK Application. The purpose of this study was to describe the perceptions of students of the Indonesian Language and Literature Education study program towards the use of the SYAM-OK application. This research is quantitative descriptive. The method used in this study is a survey method with data collection techniques using a questionnaire. Research data obtained from respondents' answers via Google Form. The results of the accumulation state that in terms of perceived ease of use, respondents' answers are in the "appropriate" category with a percentage of 78% choosing the statement "agree". On the perception of usefulness, respondents' answers are in the "adequate" category with a percentage of 83% choosing the "agree" statement. While on the acceptance of acceptance, the respondent's answer is in the "very feasible" category with a proportion of 100% choosing "agree". It can be said that SYAM-OK is suitable for use in the learning process of students of the Indonesian Language and Literature Education study program.